Nonlinear control of quadrotor trajectory with discrete H - Hasanlu, M.; Siavashi, M. (Journal of Mechanical Engineering Automation and Control Systems, 2025)
Fixed-wing drones generate lift using a wing similar to a conventional airplane, in contrast to rotary helicopters. As a result, these machines use energy solely for propulsion rather than to maintain altitude, making them significantly more efficient. These devices can traverse greater distances and cover larger areas, making them capable of mapping and monitoring specific points over extended periods. This article uses an analytical nonlinear approach to look at how discrete H ∞ can be used as a robust controller to manage the path of a quadrotor. The main goal is to create a discrete H ∞ nonlinear output feedback algorithm that can accurately track the position of the quadrotor while staying stable, even when there are unknowns, disturbances, or noise. The discrete formulation of this algorithm makes it especially suitable for multi-engine aircraft. By designing the controller in a discrete space first, transitioning to a continuous phase, and then reverting to discrete space for real-world application, more desirable and design-aligned results can be achieved. However, transitioning from continuous to discrete controllers may sometimes cause deviations from the design specifications. Designing the controller directly in the discrete space simplifies the overall process and enhances robustness.